Basic skills for home care aides - Deihl, Adrianne; Bohunicky, Marty; Bradley, Mickey; Thomson Delmar Learning ([s.l.] : Thomson Delmar Learning, 2005)
This program presents the prosedures needed for home care aides and focusing on body mechanics and rehabilitation skills
Title from title screen
Segment 3 : Body mechanics ; segment 4 : rehabilitation skills
Camera, Dominick Figliomeni, Kevin Keithley
Narrator: Yvonne Perry
Keywords: Home Health Aides; Home care services; Nurses' Aides